Household air pollution as a determinant of health status: A study on older adults in Siliguri Municipal Corporation, India - Manik Halder; Nuruzzaman Kasemi (Scientific Reports)
Abstract Household air pollution (HAP), stemming from solid fuels, traditional cooking practices, and indoor pollutants like incense and mosquito oils, poses severe health risks, particularly for older adults. This study assesses the impact of HAP on self-reported health (SRH) among older adults in Siliguri municipal corporation, India. A cross-sectional survey of 400 older adults used multiple binary logistic regression to analyze HAP’s impact on poor SRH. Solid fuel use, traditional cooking, lack of ventilation, and exposure to mosquito oil and family smoking were significantly linked to poorer health. Findings underscore the need for policy measures to reduce HAP through cleaner energy and ventilation improvements, aligning with SDG 7 goals to enhance the health of vulnerable populations.